2002
DOI: 10.1007/bf02465460
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stratification and use of vegetation and light habitats by Neotropical forest birds

Abstract: SummaryThe vertical stratifcation of bird species has been intensively studied in both temperate and tropical bird communities. I investigated the vertical stratification of bird species and their use of vegetation structures and light habitats using observation data from 92 rainforest species. Most observations were made from a 40 m high canopy crane situated close to the Surumoni river (65°40'W, 3°10'N) near Esmeralda, Estado Amazonas, southern Venezuela. Further observations were made at several forest site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 46 publications
3
71
1
3
Order By: Relevance
“…This can consequently facilitate increased awareness about the biodiversity and conservation value of both primary and regenerating tropical forests [58]. Understanding the effects of anthropogenic disturbance to canopy environments is particularly important given that a number of different taxonomic assessments have suggested that biodiversity within canopy strata is under greatest threat due to habitat modification [4,[7][8][9][10][11]59]. Here we suggest that the arboreal camera trapping method can be both useful and cost-effective in the long term for conservation assessments and can provide opportunities to learn more about some of the most charismatic [12] and threatened species in the world [38,39,54] which may otherwise remain largely unknown and could quietly disappear from our planet.…”
Section: Implications For Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…This can consequently facilitate increased awareness about the biodiversity and conservation value of both primary and regenerating tropical forests [58]. Understanding the effects of anthropogenic disturbance to canopy environments is particularly important given that a number of different taxonomic assessments have suggested that biodiversity within canopy strata is under greatest threat due to habitat modification [4,[7][8][9][10][11]59]. Here we suggest that the arboreal camera trapping method can be both useful and cost-effective in the long term for conservation assessments and can provide opportunities to learn more about some of the most charismatic [12] and threatened species in the world [38,39,54] which may otherwise remain largely unknown and could quietly disappear from our planet.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Part of this complexity is evident in the vertical stratification of different faunal communities between terrestrial and canopy layers [3][4][5][6][7]. Research suggests that arboreal rainforest mammal species should be high conservation priorities because habitat alteration due to anthropogenic activities causes a greater disruption to arboreal than to terrestrial biodiversity [4,[7][8][9][10][11] and, as with rainforest mammals in general, they are often prey to human disturbance in the form of hunting.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers consider that the degree of structural complexity of phytocoenosis is a significant index of relationships between bird's communities and forest compositions (James, Wamer, 1982;Hinsley et al, 1995) and the approaches to issues based on the measurement phytocoenotic parameters and species diversity and density of breeding birds (Kurlavichus, 1986;Fuller, Moreton, 1987;Catsadorakis, 1997;Walther, 2002). The integral criterion that combines several measurement values, in particular indices of vertical and horizontal heterogeneity, is also used (MacArthur R., MacArthur J., 1961;Wilson, 1974;O´Connor, 1981;Willson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Given that predators such as birds also partition forest microhabitats (e.g. Walther 2002), this could contribute to the stable coexistence of multiple mimicry rings (Beccaloni 1997b).…”
Section: Introductionmentioning
confidence: 99%